Case for Consideration: A 30-year-old HIV-positive man with psoriasis (Canadian Dermatology Today, 2020)
You are seeing a 30-year-old man with a history of established psoriasis in your outpatient dermatology clinic. The patient has well-controlled human immunodeficiency virus (HIV) and he takes a new antiretroviral (ARV) medication, Biktarvy®. The patient’s HIV in the blood is undetectable and his CD4 T-cell count is normal. His health is otherwise good.  During the clinical workup, he mentions that his partner is HIV-negative and is on pre-exposure prophylaxis (PrEP) medication and has developed brown facial spots and is wondering if the PrEP medication may have caused this and also wants to see a dermatologist.The patient starts on combination calcipotriene / betamethasone dipropionate foam and considers phototherapy. Upon reviewing the data on Biktarvy®, you become aware that it causes “rash” and wonder about interactions with acitretin, cyclosporine, or methotrexate. Biktarvy® contains bictegravir, emtricitabine and tenofovir alenamide. It does not contain ritonavir.HIV and its treatment have changed significantly over the past 30 years. The virus can be fully suppressed with antiretroviral therapy (ARV), formerly known as highly active antiretroviral therapy (HAART). If ARVs are accessible and started early, collaborative cohort studies across Europe and North America demonstrate improved survival & life expectancy. There are now no threshold levels for initiation of ARVs based on CD4 T-cell count or viral load, if the ARVs are accessible to the patient. Treatment is generally recommended after diagnosis of HIV.